Serum from morbidly obese patients affects melanoma cell behavior in vitro - Débora Mocellin; Letícia de Oliveira Souza Bratti; Adny Henrique Silva; Laura Sartori Assunção; Iara Fabricia Kretzer; Fabíola Branco Filippin-Monteiro (Universidade de São Paulo, 2022)
Abstract Here we examined whether serum from obese patients could create a growth-enhancing microenvironment that alters gene expression in BRAF- and NRAS-mutated melanoma cell lines. SK-Mel-28 (BRAF-mutated) and Sk-Mel-147 (NRAS-mutated) cells were treated with pooled serum from 10 severely obese patients (BMI > 40 kg/m2), pooled serum from 6 healthy lean individuals (BMI = 18.5-24.9 kg/m2), or recombinant TNF-α. We found that obese patient serum enhanced migration capacity and increased NRAS expression levels in both BRAF- and NRAS-mutated melanoma cells. Although TNF-α is the major obesity-related cytokine and TNF-α levels were found to be increased in the serum of obese individuals, this cytokine made only a modest contribution to the migration capacity of melanoma cells. These results indicate that other components present in the serum of severely obese patients may be responsible for enhancing the migration capacity of melanoma cells. As TNF-α alone did not seem to significantly affect tumor cell behavior, anti-tumor strategies aimed at blocking TNF-α should be considered with caution in future studies, particularly when in vitro models are used as screening platforms for antitumor activity.